"[Drinking is] Like a Rule That You Can't Break": Perceived Barriers and Facilitators to Reduce Alcohol Use and Improve Antiretroviral Treatment Adherence among People Living with HIV and Alcohol Use Disorder in Vietnam. (7th June 2018) - Hershow, Rebecca B.; Zuskov, Diana S.; Vu Tuyet Mai, Nguyen; Chander, Geetanjali; Hutton, Heidi E.; Latkin, Carl; Vuong, Nguyen Duc; Sripaipan, Teerada; Lancaster, Kathryn E.; Ha, Tran Viet; Go, Vivian F.
ABSTRACT: Background: Alcohol use, a highly normative behavior in Vietnam that is associated with high rates of HIV infection and lower antiretroviral treatment (ART) adherence, has been largely overlooked by HIV prevention efforts. Objectives: Using the risk environment framework, this qualitative study aims to explore the perceived microenvironmental (community-level) and endogenous (individual-level) barriers and facilitators to alcohol reduction among people living with HIV (PLHIV) with alcohol use disorders (AUDs) in Vietnam. Methods: From June-July 2014, semi-structured interviews were conducted with thirty PLHIV (18 men; 12 women) recruited from an outpatient ART clinic in Thai Nguyen province, Vietnam. All participants had scores of ≥8 on the Alcohol Use Disorders Identification Test and ten of the 30 participants were currently using injection drugs. Interviews were transcribed, translated, and analyzed to identify perceived barriers and facilitators to alcohol reduction. Results: Most participants reported a spike in alcohol consumption at the time of HIV diagnosis. Most perceived barriers existed at the microenvironmental level, including perceived inability to refuse alcohol in the context of community-level social norms and lack of alcohol treatment programs. Two commonly mentioned endogenous barriers were compensatory behaviors when reducing injection drug use and using alcohol as a coping strategy for HIV-related sadness. Those who were able to successfully reduce alcohol use and adhere to ART reported having social support to buffer community-level social pressure and cope with sadness. Conclusions: It may be effective to introduce targeted alcohol reduction interventions in health care centers to address individual risk practices and microenvironmental social norms.